Pengaruh Pemberian Asuhan dengan Oil Organik terhadap Penurunan Nyeri Bendungan Asi pada Ibu Nifas - Marni Sasmita; Rani Safitri (Lembaga Pengembangan Kinerja Dosen, 2026)
Breast engorgement is one of the common problems experienced by postpartum mothers due to increased breast milk production that is not balanced by optimal milk release, causing pain, discomfort, and disruption of the breastfeeding process. Non-pharmacological management is widely used because it is considered safer and easier to apply. One alternative intervention is the use of organic oil consisting of Virgin Coconut Oil (VCO) and lemongrass as a complementary treatment. This study aimed to determine the effect of providing care using organic oil on reducing breast engorgement pain in postpartum mothers. This study used a quantitative method with a pre-experimental design using a one-group pretest-posttest approach. The sample consisted of 32 postpartum mothers experiencing breast engorgement selected through purposive sampling. Pain intensity was measured using the Numeric Rating Scale (NRS), and data analysis was performed using the Wilcoxon Signed Rank Test. The findings showed a significant effect of organic oil intervention on reducing breast engorgement pain with a significance value of 0.000 (p<0.05). Most respondents experienced a decrease in pain intensity after the intervention. The findings imply that organic oil consisting of VCO and lemongrass can be considered an alternative non-pharmacological intervention in reducing breast engorgement pain among postpartum mothers.